SÄRAT CIPTAN SABÄN ESUK Suntingan Teks dan Terjemahan - , BIMA ARIA TEJA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The thesis of a philology study of SÄrat Ciptan SabÄn Esuk which stored at Dewantara Kirti Griya Museum in Yogyakarta, with code of collection: Bb.1.251. Itâs text copied by R.M Partawiraya and R. Prawiraharja. The text contains advices in order to always take efforts for achieving our purposes of life. We must be honest of each word we said, because of by this honest word, it could become our supernaturally guide and barrier from misconduct. Therefore, those who always make effort and telling the truth, they will never fail. The text is a prose which written in Javanese script with Javanese language. This research presentation arrangement consists of: introduction